2022
DOI: 10.1186/s12891-022-05512-5
|View full text |Cite|
|
Sign up to set email alerts
|

Ultrasonographic assessment of entheseal sites of upper and lower extremities in hemodialysis patients using Madrid Sonography Enthesitis Index

Abstract: Background There is no much information about the entheseal involvement among hemodialysis (HD) patients. The aim of this study was to assess the frequency and distribution of ultrasonographic (US) entheseal alterations in HD patients and to evaluate the association between US abnormalities and both clinical and laboratory data. Methods This study was conducted on 41 HD patients and 23 sex- and age- matched controls. All participants were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In this study, we found that the prevalence of MSUS abnormalities was correlated with much higher clinical manifestations. In fact, subclinical musculoskeletal conditions, such as asymptomatic subclinical enthesopathy, have been identified in HD patients [17].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that the prevalence of MSUS abnormalities was correlated with much higher clinical manifestations. In fact, subclinical musculoskeletal conditions, such as asymptomatic subclinical enthesopathy, have been identified in HD patients [17].…”
Section: Discussionmentioning
confidence: 99%
“…Following the publication of the original article [ 1 ] the authors would like to correct the declared corresponding author as “Samar Tharwat” rather than “Reham Sabry”.…”
mentioning
confidence: 99%